IMPROVING STUDENT CHARACTER EDUCATION THROUGH CITIZENSHIP EDUCATION LEARNING AT SD IT AL AMIN - Sopian Sopian (Jurnal Scientia, 2023)
At this juncture, character education is required in order to shape the subsequent generation into one of better quality. This can be accomplished by cultivating a feeling of responsibility in one's approach to the period of globalization. Children's intellectual, physical, social-emotional, artistic, and spiritual growth can all benefit from receiving an education that focuses on developing good character. The purpose of this research is to enhance the Character V education offered at SD IT Al Amin Ngamprah, which is located in the West Bandung Regency. Because Citizenship Education is not only about citizenship, but there is also an inculcation of values and morals, so it has a very positive impact on sustainability in an effort to increase values and morals for elementary school students, the findings of the research show that Pancasila and Citizenship Education play an important role in the formation of the character of good citizens. This is because Citizenship Education is not only about citizenship, but there is also an inculcation of values and morals. This is demonstrated by the findings of a study that was carried out on students in the fifth grade at SD IT Al Amin Ngamprah to determine the role that Citizenship Education plays in improving the character of students, particularly with regard to the values of love for one's motherland, respect for religious beliefs, honesty, and tolerance toward others. Learning is influenced by elements such as those related to families, those related to environments, and those related to instincts.